2020
DOI: 10.1002/admi.201901665
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport Characteristics of Surface‐Complexed Quantum Dot in a Thin Film Transistor

Abstract: Ambipolar transport characteristics of thin film transistors fabricated from nontoxic white light emitting quantum dot complexes (QDCs) are herein reported to exhibit efficient carrier mobilities. The QDCs are synthesized by forming bluish green emitting zinc quinolate complex on the surface of orange emitting Mn2+‐doped ZnS quantum dots (Qdots) using 8‐hydroxyquinoline 5‐sulfonic acid as the chelating ligand. The device exhibits efficient ambipolar transport characteristics with high ION/IOFF ratio of 104 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…[6][7][8][9][10][11] At present, the transistor synapse device has attracted much attention due to its three-terminal structure with greater modulation flexibility. [12][13][14][15][16][17][18] In transistor synapse device, modulated physical quantities (such as conductance, current, etc.) like synaptic weight updating and synaptic devices can be used to implement basic and important presynaptic and postsynaptic information transmission and effectively simulate short-term, long-term memory, frequency dependence, long-term potentiation and long-term depression of biological synapses.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11] At present, the transistor synapse device has attracted much attention due to its three-terminal structure with greater modulation flexibility. [12][13][14][15][16][17][18] In transistor synapse device, modulated physical quantities (such as conductance, current, etc.) like synaptic weight updating and synaptic devices can be used to implement basic and important presynaptic and postsynaptic information transmission and effectively simulate short-term, long-term memory, frequency dependence, long-term potentiation and long-term depression of biological synapses.…”
mentioning
confidence: 99%
“…Recent reports on functionalized CQD-based layers comprise different types of short ligands and small capping agents. [94,95,[113][114][115] Both approaches were shown to enhance the electrical conductivity of the CQD films and their thermoelectric properties, highlighting the tremendous potential. [40,42] Table 1 summarizes the thermoelectric properties of CQD films and their use to enhance the thermoelectric properties of various inorganic, organic and hybrid semiconductors.…”
Section: P-type Lead Chalcogenide Cqdsmentioning
confidence: 99%
“…Importantly, ligand exchange methods, in addition to surface passivation, facilitate fast electron injection, which improves photoluminescence efficiency and interdot coupling and device stability. In addition, they provide control over exciton dynamics and the detection range, improve the electrode to excitonic barrier for a wide range of device interfaces, and thus have improved performance significantly over high quantum yield photodetectors. , On the other hand, species such as molecular complexes when incorporated on the surface of Qdots not only would help passivate the surface but also improve the versality and performance of the device. , We have recently defined such a composite as the quantum dot complex (QDC) and have shown that it possesses physical properties superior to the component Qdot or the complex. , It is plausible that a QDC would exhibit different charge transport properties as compared to the Qdot or the complex and thus may help fabricate superior photodetectors . Such an approach in bringing versatility to the optoelectronic properties of Qdots through the complexation on their surfaces has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 It is plausible that a QDC would exhibit different charge transport properties as compared to the Qdot or the complex and thus may help fabricate superior photodetectors. 35 Such an approach in bringing versatility to the optoelectronic properties of Qdots through the complexation on their surfaces has not been reported yet.…”
Section: ■ Introductionmentioning
confidence: 99%